2021
DOI: 10.3389/fphar.2021.693906
|View full text |Cite
|
Sign up to set email alerts
|

Tirbanibulin Attenuates Pulmonary Fibrosis by Modulating Src/STAT3 Signaling

Abstract: Tirbanibulin (KX-01) is the first clinical Src inhibitor of the novel peptidomimetic class that targets the peptide substrate site of Src providing more specificity toward the Src kinase. This study assessed the impact of KX-01 on cobalt chloride (CoCl2)-treated L929 cells and bleomycin (BLM)-induced pulmonary fibrosis in rats to evaluate the efficacy of this compound in vitro and in vivo, respectively. In CoCl2-treated L929 cells, KX-01 significantly reduced the expression of smooth muscle actin (α-SMA), coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Vandetanib and Ponatinib are multi-tyrosine kinase inhibitors, approved by FDA to treat CML, thyroid carcinoma, and Philadelphia chromosome-positive acute lymphoblastic leukaemia in adults 31 , 32 . Other promising c-Src inhibitors (in phase I or II, ( Figure 2 ) are DGY-06–116 33 , eCF506 34 , Elzovantinib (TPX-0022) 35 , and Tirbanibulin, the latter targeting the Src substrate binding site 36 and recently approved for the topical treatment of actinic keratosis 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Vandetanib and Ponatinib are multi-tyrosine kinase inhibitors, approved by FDA to treat CML, thyroid carcinoma, and Philadelphia chromosome-positive acute lymphoblastic leukaemia in adults 31 , 32 . Other promising c-Src inhibitors (in phase I or II, ( Figure 2 ) are DGY-06–116 33 , eCF506 34 , Elzovantinib (TPX-0022) 35 , and Tirbanibulin, the latter targeting the Src substrate binding site 36 and recently approved for the topical treatment of actinic keratosis 37 .…”
Section: Introductionmentioning
confidence: 99%
“…This could be explained by the enhanced uptake and prolonged action of CHALT. In addition, we further determined the activation of upstream SRC [45] , and the results showed that CHALT also exerted significant inhibitory effect on the phosphorylation of SRC ( Fig. 4 G and 4 H).…”
Section: Resultsmentioning
confidence: 95%
“…In a study on pulmonary fibrosis, Wang et al found that KX-01 attenuated pulmonary fibrosis by inhibiting the p-Src/p-STAT3 signaling pathway in BLM-induced pulmonary fibrosis rats. [ 27 ] Akt1, an isoform of protein kinase B, can be involved in a variety of cellular functions such as survival, metabolism, transcription and translation in the human body after being activated by various signals. Nie et al found that macrophage-specific Akt1 deletion attenuated BLM-induced Idiopathic pulmonary fibrosis and ultimately concluded that Akt1 may regulate pulmonary fibrosis through upregulation of macrophage-derived IL-13.…”
Section: Discussionmentioning
confidence: 99%